Renal function and associated mortality risk in adults commencing HIV antiretroviral therapy in Zimbabwe. (1st April 2022) - Drak, Douglas; Shamu, Tinei; Heron, Jack E.; Chimbetete, Cleophas; Dahwa, Rumbi; Gracey, David M.
Abstract : Background: People with HIV (PWH) in sub-Saharan Africa appear to have a higher incidence of renal disease than other global regions but data are limited. This renal impairment may be associated with an increased mortality risk. Aims: To define the prevalence of renal disease and explore its association with mortality risk in a cohort from Zimbabwe commencing antiretroviral therapy (ART) for HIV infection. Methods: A retrospective study of all patients aged at least 18 years, commenced on ART for HIV infection at the Newlands Clinic in Harare, Zimbabwe between January 2007 and September 2019 was conducted. Data were extracted from electronic medical records. Patients with no baseline creatinine measurement were excluded. Baseline characteristics were assessed as potential predictors for mortality by Cox proportional hazard regression. Results: Three thousand and thirty-nine patients were eligible for inclusion. Most were female (62.1%), with a median age of 36 years (IQR 30–43). At baseline, 7.3% had an estimated glomerular filtration rate (eGFR) 90 ml/min per 1.73 m 2 or less and 11.4% had proteinuria. Over a median follow-up period of 4.6 years (IQR 2.5–6.9), the mortality rate was 8.7%. One half of deaths (49.2%) occurred within the first year. In multivariable analysis, a baseline eGFR between 60 and 90 ml/min per 1.73 m 2 [hazard ratio 2.22, 95% confidence interval (CI) 1.46–3.33, P  < 0.001] and proteinuria (hazard ratio 2.10, 95% CI 1.35–3.27, P  < 0.001) were associated with increased mortality risk. Conclusion: Baseline renal impairment was common. Both a reduced eGFR or proteinuria were independently associated with a doubling of mortality risk. These should serve as markers in the clinical setting of at-risk patients.